(Systemic) Design for Sustainable Territorial Transition: A Literature Review of State of the Art - Asja Aulisio; Silvia Barbero; Amina Pereno (DIID, 2024)
Sustainable territorial development is one of the crucial elements of most governmental strategies and action plans at the international level, which have to adapt to the local context in which they are implemented. In its different scales of application, the discipline of Design is increasingly called upon, permeating skills and tools within policy and governmental contexts that contribute to the definition of strategies to address complex problems. This paper presents a systematic literature review to map the specific declinations of the design field, with a closer look at the disciplinary areas close to Systemic Design methodologies, which are most involved in this field of research. The emerging tools and methods aim to support decision-makers or stakeholders in a necessary social, economic, and environmental transition process.